Groundnut response to ash, phosphorus, potassium, lime, and tillage in southern Cameroon - Wendt, J. (Informa UK Limited, 2002)
Groundnut (Arachis hypogaea L) is an important intercrop in southern Cameroon. Two on-farm experiments were undertaken to determine if soil fertility constraints, varieties and tillage practices were major limiting factors in groundnut production. In Experiment I, combinations of P and K fertilizers and ash were applied to local groundnut. and ash to improved groundnuts (var. A-26). In Experiment 2, ash and dolomitic lime were tested with a local variety, combined with ridging or no ridging, and ash applied to a variegated Virginia (VV) groundnut variety. The experiments were conducted in six villages in southern Cameroon. Soil analytical variables were covariates in the analysis of variance. Groundnut yields were affected by significant ash × calcium saturation (Ca sat'n) and lime × Ca sat'n interactions. Where ash or lime was applied, yields were improved where Ca sat'n levels were below 0.62, but decreased at higher Ca sat' n levels. Significant village × variety interactions (p < 0.05) showed that varieties A-26 and VV yielded less than the local variety in several villages. P, K or tillage did not improve yields over the control. Both liming and ash applications increased soil pH, exch. Ca and Mg, and decreased exch. AI, while P + K applications increased exch. K and extractable P. The results show that ash application significantly influences several soil chemical variables. While yield increases in local groundnut yields can be realized at sites where Ca sat'n is low from either lime or ash applications, such increases are relatively minor. Alternative varieties tested offered no advantage over local varieties already grown in the area.